Annual Meeting of the International Society of Cancer Metabolism (ISCaM): Cancer Metabolism - Avnet, Sofia; Baldini, Nicola; Brisson, Lucie; De Milito, Angelo; Otto, Angela M.; Pastoreková, Silvia; Porporato, Paolo E.; Szabadkai, Gyorgy; Sonveaux, Pierre (Frontiers in Oncology, 2018)
Tumors are metabolic entities wherein cancer cells adapt their metabolism to their oncogenic agenda and microenvironmental influences. Metabolically different cancer cell subpopulations collaborate to optimize nutrient delivery with respect to immediate bioenergetic and biosynthetic needs. They can also metabolically exploit host cells. These metabolic networks are directly linked with cancer progression, treatment, resistance and relapse. Conversely, metabolic alterations in cancer are exploited for anticancer therapy, imaging and stratification for personalized treatments. These topics were addressed at the 4th annual meeting of the International Society of Cancer Metabolism (ISCaM) in Bertinoro, Italy, on 19-21 October 2017.